Seeking a Language that Heals: Teaching and Writing from a Ruined Landscape - Amy Nolan (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
I first heard Iowa referred to as a "ruined landscape" when I was riding a shuttle bus from an airport to a conference... The statement led me to wonder... what does "ruined" mean?